2012
DOI: 10.4082/kjfm.2012.33.5.320
|View full text |Cite
|
Sign up to set email alerts
|

Improved Chronic Fatigue Symptoms after Removal of Mercury in Patient with Increased Mercury Concentration in Hair Toxic Mineral Assay: A Case

Abstract: Clinical manifestations of chronic exposure to organic mercury usually have a gradual onset. As the primary target is the nervous system, chronic mercury exposure can cause symptoms such as fatigue, weakness, headache, and poor recall and concentration. In severe cases chronic exposure leads to intellectual deterioration and neurologic abnormality. Recent outbreaks of bovine spongiform encephalopathy and pathogenic avian influenza have increased fish consumption in Korea. Methyl-mercury, a type of organic merc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Other studies have also shown that higher urine mercury concentrations are associated with serum cholesterol concentration and cardiovascular disease 26 27. Hair sampled mercury concentrations were found to affect cardiac autonomic activity 28 29. In this study, subjects who had blood mercury concentration around 3.95 μg/L and 3.40 μg/L showed significantly higher BMI and waist circumference in males and females after adjusting for relevant confounders.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies have also shown that higher urine mercury concentrations are associated with serum cholesterol concentration and cardiovascular disease 26 27. Hair sampled mercury concentrations were found to affect cardiac autonomic activity 28 29. In this study, subjects who had blood mercury concentration around 3.95 μg/L and 3.40 μg/L showed significantly higher BMI and waist circumference in males and females after adjusting for relevant confounders.…”
Section: Discussionmentioning
confidence: 53%
“…1,4,5 A vivid example of mercury poisoning was seen in the Minamata incidence in the 1950s in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…If these workers are exposed to several dietary sources of mercury like fish or shellfish, mercury levels in their bodies could increase substantially leading to more intense health consequences [ 3 ]. Meanwhile, previous studies have mainly focused on the health effects due to acute mercury exposure and the occupational mercury sources among workers [ 6 8 ]. However, considering the effects of dietary sources on mercury levels, detailed information on dietary sources is needed during the health examinations, particularly, among the workers in Gyeongsangbuk-do, who are likely to consume a lot of shark meat.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the health effects due to acute mercury exposures [ 6 8 ]. Recently, concerns on the effects of chronic, low-dose mercury exposure on health have increased.…”
Section: Introductionmentioning
confidence: 99%